Five children on the Western Front - Saunders, Kate 1960-2023 (Faber & Faber, 2014)
Have you ever wondered what happened to the Five Children and It characters when the First World War began? Cyril is off to fight, Anthea is at art college, Robert is a Cambridge scholar and Jane is at high school. The Lamb is the grown up age of 11, and he has a little sister, Edith, in tow. The sand fairy has become a creature of stories ...until he suddenly reappears. The siblings are pleased to have something to take their minds off the war, but this time the Psammead is here for a reason, and his magic might have a more serious purpose. Before this last adventure ends, all will be changed, and the two younger children will have seen the Great War from every possible viewpoint - factory-workers, soldiers and sailors, nurses and the people left at home, and the war's impact will be felt right at the heart of their family
"An epic, heart-wrenching follow-on from E. Nesbit's Five children and It stories"--Back cover
Keywords: World War (1914-1918); World War, 1914-1918 / Juvenile fiction; Fairies / Juvenile fiction; Children's stories; Fairies; Weltkrieg (1914-1918); Erster Weltkrieg; Jugendbuch